Thousand words about alcohol use disorder in inflammatory bowel disease - Wietrzykowska, Dominika; Neubauer, Katarzyna (Journal of Medical Science, 2021)
Patients with inflammatory bowel disease (IBD), especially those with severe disease and extraintestinal manifestations, are more frequently affected by anxiety and depressive disorders compared to the healthy population. This in turn may favour the expansion of alcohol use disorders but the role of alcohol consumption in the development of IBD and its impact on IBD course remains controversial. Importantly, ethanol is a significant factor contributing to liver failure and increased risk of various malignancies, including colorectal cancer (CRC). Primary sclerosing cholangitis (PSC) is a fatal extraintestinal manifestation of IBD leading to liver failure and promoting the development of cholangiocarcinoma and colorectal cancer. Indeed, alcohol abuse by patients with IBD and PSC may promote the progression of those complications but is difficult to diagnose. The underlying disease may cause similar abnormalities in laboratory and imaging tests to ethanol thus masking the problem, therefore gastroenterologists should pay special attention to the alcohol consumption of IBD patients.